Integrated management of purple blotch disease complex for onion seed production in Bangladesh (Bangladesh Journal of Agriculture, 2022)
Onion suffers from many diseases and among them purple blotch complex is devastating for both bulb and seed production in Bangladesh. To formulate an integrated approach for its management, different IPM components viz. three fungicides viz. Rovral 50 WP (Iprodione), Dithan M-45 (Mancozeb) and Score 250 EC (Difenconazol); two botanicals viz. Alamanda leaf extract (Allamanda cathartica) and Neem leaf extracts (Azadiracta indica); four soil amendments viz. Poultry manure, bioagent, saw dusts and micronutrients (Zn @ 0.45/L +B @ 2.5g/L) were evaluated under field condition. The experiment was conducted at the farm of Sher-e-Bangla Agricultural University, Dhaka, during 2011-2012. Pathogeninicity test indicated that Alternaria porri and Stemphylium vesicarium were the pathogens where S. vesicarium initiated the infection and A. porri facilitated the subsequent infection and made a complex form of disease. Among the chemical fungicides, Score 250 EC was found promising followed by Rovral 50 WP against purple blotch complex in terms of reduction of disease incidence and severity ultimately contributing to increased yield (134% and 129%, respectively) over control. Among botanicals, Alamanda leaf extract produced better result compared to neem leaf extract (99.6% and 67.6% respectively). In terms of increasing yield, poultry manure showed better performance (72.3%) followed by micronutrient (69.5%) and bioagent (58.2%).Bangladesh J. Agri. 2019-2021, 44-46: 31-44